(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2019)
One of the main goals of regulating broadcasting programs is protecting the audience from content that can cause harm or damage the consumer. When it comes to advertising consumers should be protected from fake or misleading advertising messages. Moreover, another goal of regulating broadcasting is the protection of the freedom of expression and the democratic values of the society, fostering and developing cultural identity, promoting tolerance and cultural dialogue. In the paper we will address the regulatory measures for the protection of democratic principles and values and individual rights such as: the right to privacy, protection of dignity, protection against harm, the right to reply and correction. We will also look at the regulatory aspects of the protection of minors from content that may adversely affect the development of children, recognition and protection from hate speech, content that incites crime, disorder or racial, religious or ethnic hatred and intolerance.